The Influence of Think Pair Share (TPS) Cooperative Learning Model and Initial Ability on Learning Outcomes Biology Class VIII of SMPN 38 Sijunjung - Rini Silvina (Kurikulum Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2018)
The aim of this research was to reveal the influence of Think Pair Share cooperative learning model and initial ability on learning outcomes biology class VIII of SMPN 38 Sijunjung. This was a Quasi Experimental research which used 2 x 2 factorial design. The population of the research was the students in class VIII os SMPN 38 Sijunjung in academic year 2015/2016. By using saturated sampling technique, class VIII1 was chosen as the experimental class and class VIII2 was as the control class. The instruments of the research were posttest which was intended to identify the students’ learning outcomes. The results of the research revealed that (1) Think Pair Share cooperative learning model exerted an influence upon learning outcomes of the students having either high or low initial ability, (2) there was no interaction between Think Pair Share cooperative learning model and the students’ initial ability toward the students’ learning outcomes in Biology.